2018
DOI: 10.1002/pc.25043
|View full text |Cite
|
Sign up to set email alerts
|

PVDF/halloysite nanocomposite‐based non‐wovens as gel polymer electrolyte for high safety lithium ion battery

Abstract: Gel polymer electrolyte (GPE) based on electrospun poly(vinylidene fluoride) (PVDF)/halloysite nanotube (HNT) nanocomposite non-wovens was synthesized and its suitability as a separator in lithium-ion battery (LIB) was explored. In this study, HNT played a key role in reducing the average diameter of the electrospun fibers and uplifted the porosity of the non-wovens thereby improving their electrolyte uptake. Due to a reduction in crystallinity and increased % porosity of the PVDF/HNT non-wovens, the ionic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 107 publications
0
16
0
Order By: Relevance
“…Figure 9 shows the flame test of the membrane soaked with commercially carbonated organic electrolyte and the ionic liquid. A gel polymer electrolyte (GPE) based on electro-spun polyvinylidene fluoride (PVDF)/halloysite nanotube (HNT) nanocomposite non-wovens was synthesized and used as a separator for Li-ion batteries [41]. The GPE as a separator exhibited minimal thermal shrinkage and higher melting temperature which was proven to be important for obtaining a safer Li-ion battery.…”
Section: Gel Polymer Electrolytesmentioning
confidence: 99%
“…Figure 9 shows the flame test of the membrane soaked with commercially carbonated organic electrolyte and the ionic liquid. A gel polymer electrolyte (GPE) based on electro-spun polyvinylidene fluoride (PVDF)/halloysite nanotube (HNT) nanocomposite non-wovens was synthesized and used as a separator for Li-ion batteries [41]. The GPE as a separator exhibited minimal thermal shrinkage and higher melting temperature which was proven to be important for obtaining a safer Li-ion battery.…”
Section: Gel Polymer Electrolytesmentioning
confidence: 99%
“…They received piezoelectric PVDF fibers with a small diameter, smooth surface morphology, and appropriate β-phase at a velocity of 1900 rpm. Recent works support the view that increasing of the rotational speed of the collector induces a higher content of the piezoelectric β-phase [182][183][184].…”
Section: Synthetic Polymers Polyvinylidene Fluoridementioning
confidence: 77%
“…Halloysite is another kind of clay which has the capability to enhance the thermal stability and mechanical strength when used as filler with polymers. Khalifa et al reported composite separator based on PVDF and Halloysite nanotubes developed through electrospinning technique. The PVDF/Halloysite nanotubes composite separator shows 0% thermal shrinkage upon heating at 130 °C for 8 h and high mechanical strength of (31 MPa) as compared to bared PVDF separator.…”
Section: Types Of Separatorsmentioning
confidence: 99%